1999
DOI: 10.1038/13031
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Suppressor-of-Fused modulates nuclear–cytoplasmic shuttling of GLI-1

Abstract: Sonic hedgehog, Patched and Gli are components of a mammalian signalling pathway that has been conserved during evolution and which has a central role in the control of pattern formation and cellular proliferation during development. Here we identify the human Suppressor-of-Fused (SUFUH) complementary DNA and show that the gene product interacts physically with the transcriptional effector GLI-1, can sequester GLI-1 in the cytoplasm, but can also interact with GLI-1 on DNA. Functionally, SUFUH inhibits transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
425
2
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(457 citation statements)
references
References 31 publications
25
425
2
5
Order By: Relevance
“…There are several ways to regulate the activity of Gli transcription factors. First, nuclear-cytoplasmic shuttling of Gli molecules is tightly regulated (Kogerman et al, 1999;Barnfield et al, 2005;Sheng et al, 2006;Stecca et al, 2007). For example, protein kinase A is shown to retain Gli1 proteins in the cytoplasm (through a PKA site in the nuclear localization signal peptide) whereas active Ras signaling promotes Gli nuclear localization (Stecca et al, 2007).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…There are several ways to regulate the activity of Gli transcription factors. First, nuclear-cytoplasmic shuttling of Gli molecules is tightly regulated (Kogerman et al, 1999;Barnfield et al, 2005;Sheng et al, 2006;Stecca et al, 2007). For example, protein kinase A is shown to retain Gli1 proteins in the cytoplasm (through a PKA site in the nuclear localization signal peptide) whereas active Ras signaling promotes Gli nuclear localization (Stecca et al, 2007).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…Potential GLI-binding sites were mutated at positions 6 and 7 to G and AP-1-binding sites JUNBS1 and JUNBS2 were mutated as described in Angel et al (1988b) and Stein et al (1992) using the QuickChange site-directed mutagenesis kit (Stratagene, La Jolla, CA, USA). GLI1, GLI2, GLI2act, GLI3act, JUN, SUFU expression constructs have been described previously (Schutte et al, 1989;Kogerman et al, 1999;Eichberger et al, 2008).…”
Section: Cloning Of Promoter and Expression Constructsmentioning
confidence: 99%
“…As Drosophila Sufu is also a member of the hedgehog signaling complex, and there is evidence indicating that it functions to keep full-length Ci transcription activator in a stable but inactivated state, the mammalian Sufu may play an analogous role in primary cilia. However, in Drosophila salivary gland and in transfected mammalian cells, the most readily assayable activity of Sufu is to restrict Ci/ Gli1 from entering the nucleus (Kogerman et al, 1999;Sisson et al, 2006). It is not clear whether this activity requires the functional integrity of primary cilia.…”
Section: Ubiquitination-mediated Degradation Of Sufu S Yue Et Almentioning
confidence: 99%
“…Genetic and biochemical studies indicated that Drosophila Sufu binds, stabilizes and retains Ci (Cubitus interruptus) in the cytoplasm (Monnier et al, 1998;Ohlmeyer and Kalderon, 1998;Ingham and McMahon, 2001). These biochemical activities of Sufu are conserved in mammals (Kogerman et al, 1999;Jacob and Lum, 2007), and mammalian Sufu was also found to possess a nuclear activity in repressing Gli-mediated transcription via its interaction with SAP18 (Cheng and Bishop, 2002), a component of the Sin3-HDAC corepressor complex. Sufu mutations are present in 9% of medulloblastoma patients (Taylor et al, 2002), and mice that carry one target-inactivated Sufu allele exhibited heightened risk of developing medulloblastoma in p53 null background (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%